Knowledge and compliance with the care of central catheters in a Mexican Hospital - Vázquez-Espinoza, José Antonio; Alcaraz - Moreno, Noemí; Godínez Gómez, Rubén (Revista Cuidarte, 2020)
Introduction: The use of intravascular catheters is a fundamental tool for patient care, which has been associated with nosocomial bacteraemias between 15 and 30%. The objective of the study was to determine the level of knowledge and compliance of nurses regarding the protocol for central vascular access care. Materials and methods: descriptive, cross-sectional, observational study, which included 67 nursing professionals who took care of patients with central venous catheter. For the collection of data, two instruments designed from the care protocol issued by the Permanent Nursing Commission were used. Results: Personnel with an average working age of 7.9 years were found. In knowledge, 58.2% was placed in the Meet category, in contrast to compliance resulting in 91% of the staff in the Meet category. There was no correlation between knowledge and compliance (rho = -0.181, p = 0.797). Discussion: Compliance contrasted with knowledge, however, the statements for both variables were related to the lack of handwashing, leaving adequate time for antiseptics and disinfection of lumens at the time of manipulation. Conclusions: The lack of knowledge and compliance with elements of the protocol are directly related to procedural situations performed by the nursing professional, so there is no lack of material and inputs factors to not follow the standardization of care.
Keywords: Nursing; Central Venous Catheters; Knowledge; Compliance